Saturday

August 23, 2014

August 23, 2014

Posted by **Tomika** on Wednesday, June 13, 2007 at 3:43pm.

1. 2x^2-5x=3

2. 3x^2-2x+1=0

Rearrange the equation in quadratic formula form.

2x^2 -5x -3 = 0

Then use the formula. Tell me what you don't understand about it if you don't know what to do next.

I am just not good in math at all and I was needing assistance, I am not sure on how to even start it...

We provide assistance in the form of hints to help you get started. But we leave the smaller details to you. We don't DO the homework but we help you do it. To do the first one, make the equation, as I suggested above, read

2x2 -5x -3 = 0.

Remember the quadratic formula is

x = [-b +/- sqrt (b^2 - 4ac)]/2a

where a is the coefficient of the x^2 term, b is the coefficient of the x term and c is the constant. In this case, a is 2, b is -5 and c is -3. Plug those values into the quadratic formula and solve for x

**Related Questions**

math - (4.35E-2 - x)(7.56E-2 -x ) ============================ (0.324 + 2x)2 ...

quadratic equations - can you solve the equation using the quadratic formula x2...

algebra II - I'm quite clueless as to how to solve this. I know the quadratic ...

math-calculus - solve equation |x^2-2x-6| using quadratic formula. i not get how...

math,algebra - can someone help me out factor out this 0=16t^2-122t+180 i have ...

math,correction - Problem 10 use the quadratic formula to solve each of the ...

algebra - which quadratic formula would be used to solve the following quadratic...

Algebra 2 - Can you show your work please :/ 12. Use the quadratic formula to ...

algebra - Solve the quadratic equation: 2x(squared)+6x+12=0 I know you have to ...

math - 15t^2+7t=2 The quadratic formula tells you that the solutions are: t = [-...